Effect of indium droplets on growth of InGaN film by molecular beam epitaxy. (January 2018) - Zheng, Xiantong; Liang, Hongwei; Wang, Ping; Sun, Xiaoxiao; Chen, Zhaoying; Wang, Tao; Sheng, Bowen; Wang, Yixin; Chen, Ling; Wang, Ding; Rong, Xin; Li, Mo; et al.
Abstract: Effect of indium (In) droplets on InGaN thin films grown by molecular beam epitaxy (MBE) has been investigated. The surface of InGaN covered by In droplets shows a smoother topography than that without droplets, indicating that the presence of In droplets is beneficial to the two dimensional growth. Beneath the In droplets, many ring-like structures are observed. The arrangement of these "ring" shows the movement of the In droplets during the InGaN growth. A qualitative growth model is proposed to explain the evolution of the InGaN surface morphology in In-droplet-induced-epitaxy process, giving an explanation that a local vapor-liquid-solid (VLS) system is preferentially formed at the edge of the droplets, leading to a high growth rate. Furthermore, the energy dispersive X-ray spectroscopy results reveal that the relatively higher In/Ga flux ratio in the region covered by the In droplet results in a locally higher In content. Highlights: The growth behavior under the droplets is different from the zones free of droplets. In droplets is beneficial to the two dimensional growth. A qualitative growth model is proposed to explain the evolution of the InGaN surface morphology in In-droplet-induced-epitaxy process. The relatively higher In/Ga flux ratio in the region covered by the In droplet results in a locally higher In content.